TO THE QUESTION FROM PREVIOUS RESEARCH OF SOCIO-ECONOMIC DEVELOPMENT OF THE REGION - Телебєнєва, Євгенія (Human Geography Journal, 2014)
The article deals with the features of social and economic development from the standpoint of scientists of different fields of science and from all over the world. The main issues and research topics at different stages of social development are identified. The basic concept of socio-economic development by various authors are considered. Revealed the problems with the positions of various scholars on the prediction and management of socio-economic development of the region. Substantiated conclusions about the relevance of this issue and further research in the future.